Experimental School for Primates: Analysis of the consistency between assumptions and empirical practices (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
This study evaluated the empirical studies of the Experimental School for Primates (ESP) in order to verify the consistency between their theoretical and empirical practices, especially the assumption of homology of behavioral processes among capuchin monkeys (Sapajus spp.) and humans. The following aspects were analyzed a) the origin of the objectives and procedures of the studies, 2) whether the objectives were achieved or not, and 3) whether in the studies of ESP the issue of animal model and/or applicability of the procedures used to study humans were discussed. It was noted that there are no empirical data supporting the homology proposal in the ESP theoretical proposition. It is suggested: 1) the development of empirical studies that validate the homology of behavioral processes among some human and capuchin monkeys repertoires, and 2) to initiate the application of basic research findings from ESP to develop procedures to teach relational repertoires for people with cognitive development delay.
Keywords: animal models; experimental school for primates; homology of behavioral processes; scientific consistency